A comprehensive review of the application of waste tire rubber in concrete/mortar as fine aggregate replacement - Hasan, K.; Rahaman, Md Mafuzur; Ali, Muaz; Urmi, Mst. Arefn Jannat; Fariha, Noshin Anjum; Islam, Md. Toriqule; Nahar, Tahmina Tasnim; Fadzil, Mat Yahaya (Springer Nature, 2023)
With the tremendous increase of automobiles nowadays, the disposal of waste tire rubber has become a prime environmental concern, presenting a vast ecological hazard in all parts of the world. One of the potential solutions is using waste tire rubber into concrete/mortar to replace fine aggregate, which reduces the consumption of raw materials, resulting in increased economic efficiency and long-term growth in the construction industry. Based on previous research, this paper reviews and summarizes waste rubber's fresh properties, mechanical properties, durability, and electrical resistivity as the partial fine aggregate substitution in mortar/concrete. The results indicate that concrete containing crumb rubber (CR) reduces workability and fresh density. However, it can be improved by adding large sizes of rubber particles. Concrete's mechanical properties tend to decrease as the CR concentration rises. Therefore, treated CR particles, fibers, and additional binders can increase the mechanical properties of concrete materials. Moreover, the proper CR concentration exhibits high freeze–thaw resistance, water absorption and permeability, concrete shrinkage, electrical resistance, abrasion resistance, carbonation, chloride ion resistance, and resistance to acid and sulphate attack. Additionally, the chemical treatment of rubber aggregates has proved to be an effective and practical means of compensating for the loss of durability and mechanical strength of concrete containing rubber.